On Some Inequalities of Differentiable Uniformly Convex Mapping with Applications. (4th April 2023) - Barsam, Hasan; Sayyari, Yamin
Abstract: The widely known hermite-hadamard-Fejer type inequalities are so important in the field of mathematical analysis. Many researchers have studied on these inequalities. In this paper, we have obtained several inequalities related to the Hermite-Hadamard inequality for a special class of the functions called uniformly convex functions. We have also presented applications of these obtained inequalities in some error estimates for higher moments of random variables.